Analysis of the Relationship between Nutritional Status, Play Activities and Physical Fitness of Children with Motor Ability - Vivi Gita Puspita; Hafizah Delyana (Universitas Negeri Padang, 2019)
Nutritional status is a condition in which each individual can be influenced by several factors such as the influence of food that is being consumed by someone is an indicator of nutritional status. A child who has a good nutritional status can be seen from the growth and development will run in a balanced and can be categorized as healthy. If a child can be said to be healthy then the child can carry out their duties properly and correctly. Adding good nutritional status is one of the requirements in achieving optimal health, well-controlled emotions, good mental health and physical appearance of children in accordance with the rules. Physical health can support the ability of a child because that ability is the level where a person can do according to what has been determined and done in the right ways also in accordance with the rules.Keywords: Nutritional Status, Physical Freshness, Early Childhood, Motor Ability